Plan de negocios para la creación de una organización sin ánimo de lucro dedicada a la prevención de las causas que llevan a los jóvenes al consumo de sustancia psicoactivas en el barrio Suba Rincón (2021)
Degree work focuses on desig ning a business plan for the creation of a non-profit organization in favor of preventing the causes that lead young people to the consumption of psychoactive substances in the Suba Rincon neighborhood. In this way, it seeks to reduce consumption and increase opportunities for young people who do not have the necessary resources and support from their families, for this the statistics of this area will be taken into account with the help of the government, encouraging them to focus on their illnesses. habits in new activities, planning strategies in which they feel more attracted and motivated.